THE KEYS TO EXCELLENCE : The Deming philosophy - Mann, Nancy R., author 338962 (London : MERCURY Book Division, 1989)
Outlines a Deming's philosophy of management which holds that, by enhancing the quality of products, overall productivity can be increased and competitiveness improved. The book also shows how the philosophy has been implemented in Japan and how this is influencing western firms.